2021
DOI: 10.1186/s12913-021-07397-x
|View full text |Cite
|
Sign up to set email alerts
|

Guideline-discordant dosing of direct-acting oral anticoagulants in the veterans health administration

Abstract: Background Clear guidelines exist to guide the dosing of direct-acting oral anticoagulants (DOACs). It is not known how consistently these guidelines are followed in practice. Methods We studied patients from the Veterans Health Administration (VA) with non-valvular atrial fibrillation who received DOACs (dabigatran, rivaroxaban, apixaban) between 2010 and 2016. We used patient characteristics (age, creatinine, body mass) to identify which patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…16 Consistent with prior, smaller studies, we found that several patient characteristics are more common in those treated with an off-label dose, including older age, weight, and dialysis dependence. 6,17 The DOACs studied (apixaban, rivaroxaban and dabigatran) account for the majority of DOAC use in the United States. 18,19 Broadly, these data provide opportunities to address this quality gap, focusing on patient profiles at-risk for off-label DOACs dose, risk of over or underdosing based on type of DOAC utilized.…”
Section: Discussionmentioning
confidence: 99%
“…16 Consistent with prior, smaller studies, we found that several patient characteristics are more common in those treated with an off-label dose, including older age, weight, and dialysis dependence. 6,17 The DOACs studied (apixaban, rivaroxaban and dabigatran) account for the majority of DOAC use in the United States. 18,19 Broadly, these data provide opportunities to address this quality gap, focusing on patient profiles at-risk for off-label DOACs dose, risk of over or underdosing based on type of DOAC utilized.…”
Section: Discussionmentioning
confidence: 99%
“…16 Consistent with prior, smaller studies, we found that several patient characteristics are more common in those treated with an off-label dose, including older age, weight, and dialysis dependence. 6,17 The DOACs studied (apixaban, rivaroxaban, and dabigatran) account for the majority of DOAC use in the United States. 18,19 Broadly, these data provide opportunities to address this quality gap, focusing on patient profiles at risk for off-label DOAC dose, risk of overdosing or underdosing based on the type of DOAC utilized.…”
Section: Discussionmentioning
confidence: 99%